Efeitos de um protocolo de exercícios físicos supervisionados em indivíduos com síndrome pós-COVID-19 - Frese, Cristiele Batista (2023)
Post-COVID-19 syndrome or long COVID is characterized as a clinical condition originating from SARS-CoV-2 infection that presents persistent symptoms that developed or continued after contamination. The objective was to evaluate the effects of a supervised exercise protocol on pain, spinal flexibility, peripheral muscle strength and functional capacity in individuals with post-COVID-19 syndrome. This is a double-blind randomized clinical trial type study. The study participants were individuals with an average age of 46.2 years, who had had COVID-19 for at least three months, and with persistent symptoms of the syndrome. The sample was divided into two groups, G1: supervised physical exercise group performed the proposed protocol twice a week, each session lasting one hour. G2: home guidance group, performed the exercises according to the home guidance booklet, distributed after the initial assessment. Results: the majority of participants were white females with incomplete higher education. Practicing a supervised physical exercise program has been shown to be effective in improving pain, flexibility and functional capacity in individuals with post-COVID-19 syndrome.